Sieve Tube Unloading and Post-Phloem Transport of Fluorescent Tracers and Proteins Injected into Sieve Tubes via Severed Aphid Stylets - Fisher, Donald B. (American Society of Plant Physiologists, 2000)
A variety of fluorescent tracers and proteins were injected via severed aphid stylets into the sieve tubes of wheat (Triticum aestivum L.) grains to evaluate the dimensions of plasmodesmal channels involved in sieve element/companion cell (SE/CC) unloading and post-phloem transport. In the post-phloem pathway, where diffusion is the predominant mode of transport, the largest molecule to show mobility was 16-kD dextran, with a Stokes radius of 2.6 nm. This suggests that the aqueous channels for cell-to-cell transport must be about 8 nm in diameter. Even the largest tracer injected into the sieve tubes, 400-kD fluorescein-labeled Ficoll with a Stokes radius of about 11 nm, was unloaded from the SE/CC complex. However, in contrast to smaller tracers (≤3 kD, with a Stokes radius ≤ 1.2 nm), the unloading of fluorescein-labeled Ficoll and other large molecules from the SE/CC complex showed an irregular, patchy distribution, with no further movement along the post-phloem pathway. Either the plasmodesmal channels involved in SE/CC unloading are exceptionally large (perhaps as much as 42 nm in diameter), with only a very small fraction of plasmodesmata being conductive, or the larger tracers damage the plasmodesmata in some way, enlarging smaller channels.